Do Non-Traditional Income, Size, and Growth Affect the Performance of the Banks? : Evidence from the Big Three Countries of South Asia - Ramzan Ali; Zahir Zahid Butt; Sami Ullah Butt (SEISENSE Journal of Management, 2019)
Purpose- The aim of this study is to examine the impact of non-traditional income, size and growth on the performance of the banks in big three economies of South Asia, as in the modern banking, non-traditional income plays a vital role by acting as a link between bank and its customers. Design- This study utilized the annual data over the period from 1996 to 2015, data were obtained from Federal Reserve Economic Data (FRED). This study examines the long-run as well as the short-run relationship among variables through the statistical technique of Panel ARDL. Findings- The findings of this study showed a significant and positive relationship between non-traditional income and return on assets as well as bank size and return on assets. While the association among the growth and return on assets is negative but significant. Policy Implications- Policy recommendation of this study suggests that banks should also explore new avenues of non-interest valued added services to their customers which will not only facilitate their customers also attract new customers which ultimately enhance the performance of the banks as well as the country.